Maternal correlates of birth weight of newborn: A hospital based study - Kaur, Samarjeet; Upadhyay, Ashok Kumar; Srivastava, Dhirendra Kumar; Srivastava, Reena; Pandey, Onkar Nath (Indian Journal of Community Health, 2014)
Background: weight of the baby at birth is considered to be a major determinant of future health and survival of the child. It is one of the important factors which determine the readiness with which the newborn baby adjusts to its surrounding. Many maternal socio-biological factors influence birth weight. Objective: To determine maternal socio-biological factors influencing birth weight of newborn. Methodology: Hospital based cross- sectional study undertaken in Obstetrics and Gynaecology ward of Nehru hospital, Gorakhpur. The study period extended from July 2011 to August 2012. The study subject included recently delivered mothers and data was collected on semi-structured interview schedule to know various socio-biological variables such as mother’s age, parity, inter-pregnancy interval etc, influencing the low birth weight of newborn. Chi-Square test was applied to observe the significance of association. Results: The overall proportion of low birth weight baby came out to be 32.06%. Out of various socio-biological factors taken the factors which came out to be statistically significant were age of mother, parity, inter-pregnancy interval, SLI, education. The factors which were not statistically significant were father’s education, religion. Conclusions: It was concluded that teenage pregnancy, non-utilization of antenatal care practices, anaemia, illiteracy are unfavorable predictors of birth weight of newborn babies.